Evaluation of Coal Mining Operation Performance by Frequency and Severity Rate of Accidents - Putri, Karina Shella; Noor, Ihsan; Ramadhan, Andi Afdal Givar; Saharani, Salma; Laili, Rizka Trisna; Fahrezi, Muhammad Irgi; Adnyza, Najwa Radila; Ningtias, Dinda Junita (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
A coal mining operation is a high-risk activity with higher accident rates. Occupational health and safety in coal mining is essential and urgent for proper handling. The performance of occupational health and safety (OHS) in mining operations is carried out by analyzing the ratio of frequency (IFR) and severity (ISR) in each period. For the case of JBG coal mining in South Kalimantan Province from 2017 to 2022, the data obtained showed no fatalities or serious (major) injuries recurring more than once in 2018, 2021, and 2022. Minor injuries occurred only once in 2018. This study aims to determine the performance of OHS in coal mining operations in South Kalimantan, Indonesia, by evaluating the statistical performance report of IFR and ISR.